Even in paradise - Philpot, Chelsey (Harper, an imprint of HarperCollinsPublishers, 2014)
When Julia Buchanan enrolls at St. Anne's at the beginning of junior year, Charlotte Ryder already knows all about her. Most people do... or think they do. Charlotte certainly never expects she'll be Julia's friend. But almost immediately, she dives headfirst into the larger-than-life new girl's world -- a world of midnight rendezvous, dazzling parties, palatial vacation homes, and fizzy champagne cocktails. And then Charlotte meets, and begins falling for, Julia's handsome older brother, Sebastian. But behind her self-assured smiles and toasts to the future, Charlotte soon realizes that Julia is still suffering from a tragedy. A tragedy that the Buchanan family has kept hidden... until now.